undamental aspects in neuromodulation methods (TMSr, tDCS) and speech and language therapy in the rehabilitation of subacute or chronic post-stroke aphasia - Julio Fuenzalida (2021)
Aphasia is one of the most common consequences after a cerebral stroke, the rehabilitation used is based on speech and language therapy (SLT). In recent years, the implementation of neuromodulation techniques, such as repeated transcranial magnetic stimulation (rTMS) and direct current transcranial stimulation (tDCS) have had a greater impact, improving the prognosis or rehabilitation time of the patient. The objective of the present review is based on explaining the most relevant advances in the rehabilitation of subacute or chronic aphasia using TLS together with neuromodulation methods (rTMS and tDCS), as well as presenting the results obtained in the different neuroanatomical areas, such as the left inferior frontal gyrus, the left primary motor cortex, the right cerebellum, or the 10th thoracic spinal vertebra.Data from some reviews and meta-analyzes were included that will relate the rehabilitation of aphasia, subacute or chronic, after a cerebral stroke using TLS together with one or both of the neuromodulation methods chosen, rTMS and tDCS. It was concluded that rehabilitation directed to the lower right frontal lobe with inhibitory stimuli showed the best results, despite this lack of more precise data to carry out the most effective method in rehabilitation.